"Militant Islam" vs. "Islamic militancy"?: religion, violence, category formation and applied research : contested fields in the discourses of scholarship - Hock, Klaus; Käsehage, Nina (Religionswissenschaft: Forschung und Wissenschaft, 2020)
Discourses on 'radical Islam', on 'Islamic extremism', or on 'religious violence' in Islamic contexts are en vogue - in and beyond academia. But in view of the highly contested topic of political Islam, the challenge starts already with the preferred terminology. What actually are we talking about when we talk about 'salafism', 'jihadism', 'Islamic terrorism', etc.? This edited volume provides a collection of contributions that due to their respective academic cultures and disciplinary locations display a multifaceted variety of approaches to the research field and its subject